Differentiation of ICOS+ and ICOS- recent thymic emigrant regulatory T cells (RTE Tregs) during normal pregnancy, pre-eclampsia and HELLP syndrome - Wagner, Miriam; Jöst, Maria; Spratte, Julia; Schaier, Matthias; Mahnke, Karsten; Meuer, Stefan; Zeier, Martin; Steinborn-Kröhl, Andrea (Clinical & experimental immunology, 2016)
Two different subsets of naturally occurring regulatory T cells (nTregs), defined by their expression of the inducible co-stimulatory (ICOS) molecule, are produced by the human thymus. To examine the differentiation of ICOS+ and ICOS−CD45RA+CD31+ recent thymic emigrant (RTE) Tregs during normal pregnancy and in the presence of pre-eclampsia or haemolysis elevated liver enzymes low platelet (HELLP)-syndrome, we used six-colour flow cytometric analysis to determine the changes in the composition of the ICOS+ and ICOS− Treg pools with CD45RA+CD31+ RTE Tregs, CD45RA+CD31− mature naive (MN) Tregs, CD45RA−CD31+ and CD45RA−CD31− memory Tregs. With the beginning of pregnancy until term, we observed a strong differentiation of both ICOS+ and ICOS−CD45RA+CD31+ RTE, but not CD45RA+CD31− MN Tregs, into CD45RA−CD31− memory Tregs. At the end of pregnancy, the onset of spontaneous term labour was associated with a significant breakdown of ICOS+CD45RA−CD31− memory Tregs. However, in the presence of pre-eclampsia, there was a significantly increased differentiation of ICOS+ and ICOS−CD45RA+CD31+ RTE Tregs into CD45RA−CD31+ memory Tregs, wherein the lacking differentiation into CD45RA−CD31− memory Tregs was partially replaced by the increased differentiation of ICOS+ and ICOS−CD45RA+CD31− MN Tregs into CD45RA−CD31− memory Tregs. In patients with HELLP syndrome, this alternatively increased differentiation of CD45RA−CD31− MN Tregs seemed to be exaggerated, and presumably restored the suppressive activity of magnetically isolated ICOS+ and ICOS− Tregs, which were shown to be significantly less suppressive in pre-eclampsia patients, but not in HELLP syndrome patients. Hence, our findings propose that the regular differentiation of both ICOS+ and ICOS−CD45RA+CD31+ RTE Tregs ensures a healthy pregnancy course, while their disturbed differentiation is associated with the occurrence of pre-eclampsia and HELLP syndrome.